Analisis Kebutuhan Bidan dan Ibu Hamil Terhadap Layanan Edukasi Kesehatan Ibu Hamil guna Mencegah BBLR - Riskha Dora Candra Dewi Dewi (Consilium Sanitatis: Journal of Health Science and Policy, 2023)
Objective: This study aims to analyze the needs of midwives and pregnant women for pregnancy education services to prevent LBW (Low Birth Weight Babies). Methods: This study used a combined approach between qualitative and quantitative approaches or commonly called the mixed method, which was conducted on 15 respondents consisting of midwives and pregnant women. Results: This research found that midwives and pregnant women need a WhatsApp-based chatbot service that is useful, easy to use and inexpensive Conclusion: Midwives and pregnant women need a whatsapp-based chatbot service that is useful, easy to use and inexpensive. This should be considered by stakeholders to be sensitive to the needs of pregnant women and midwives. The need for health literacy should indeed keep up with the times where access can be reached easily.